2003
DOI: 10.1128/aem.69.5.2692-2698.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role of Listeria monocytogenes σ B in Survival of Lethal Acidic Conditions and in the Acquired Acid Tolerance Response

Abstract: The food-borne pathogen Listeria monocytogenes can acquire enhanced resistance to lethal acid conditions through multiple mechanisms. We investigated contributions of the stress-responsive alternative sigma factor, B , which is encoded by sigB, to growth phase-dependent acid resistance (AR) and to the adaptive acid tolerance response in L. monocytogenes. At various points throughout growth, we compared the relative survival of L. monocytogenes wild-type and ⌬sigB strains that had been exposed to either brain h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
130
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(140 citation statements)
references
References 42 publications
8
130
1
1
Order By: Relevance
“…A number of transcriptional reporter systems based on bioluminescence and enzymatic assays have been used to study the regulation of transcription and the investigation of promoter activity in L. monocytogenes. [14][15][16] However, the commonly used lacZ, gus or lux reporters are limited by the need for specific cofactors or exogenous substrates. In addition to these considerations we sought a system that could be detectable with multiple methods and not adversely affected by the measurement techniques or growth conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A number of transcriptional reporter systems based on bioluminescence and enzymatic assays have been used to study the regulation of transcription and the investigation of promoter activity in L. monocytogenes. [14][15][16] However, the commonly used lacZ, gus or lux reporters are limited by the need for specific cofactors or exogenous substrates. In addition to these considerations we sought a system that could be detectable with multiple methods and not adversely affected by the measurement techniques or growth conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moorhead and Dykes (2003) showed that an L. monocytogenes serotype 1=2a wild-type strain was less resistant to nisin than a serotype 4c wild-type strain, suggesting differences in antimicrobial sensitivities among strains. It is also likely that other environmental stresses (in addition to the presence of the antimicrobial peptide) imposed upon the cells also evoke differential phenotypic responses from the cells (e.g., exposure to low pH induces s B activity in L. monocytogenes), which may provide cross-resistance to multiple stresses (Ferreira et al, 2003 immunity against SdpC (Butcher and Helmann, 2006;Ellermeier et al, 2006); therefore, we hypothesized that lmo2570 may play a role in antimicrobial immunity in L. monocytogenes. lmo2570 was predicted as s B dependent in previous microarray experiments (Kazmierczak et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Nisin's solubility and activity are optimal at pH 3 and 3.5, respectively (Abee and DelvesBroughton, 2003); therefore, nisin is typically dissolved in an acidified solution before use (Liu and Hansen, 1990;Huot et al, 1996). As s B expression and activity are induced at low pH (Becker et al, 1998;Sue et al, 2004), we predicted that addition of nisin in an acidified solution to the various cultures would upregulate expression of the s B regulon, thus conferring a survival advantage to the wild type over the DsigB strain (Wiedmann et al, 1998;Ferreira et al, 2001Ferreira et al, , 2003 and, hence, confounding interpretation of our experimental results. Therefore, to avoid induction of s B activity, nisin was dissolved in sterile distilled water (1000 AU=mL), and the pH of the final solution was adjusted to 7.0 using 0.01 N sodium hydroxide.…”
Section: Nisin Minimum Inhibitory Concentration Determinationmentioning
confidence: 99%
“…Sodium is used in various foods such as chicken broth, meat gravy, salami, bacon, cured meat and cheese, and NaCl is usually used as a sodium source. Many studies showed that NaCl increased heat resistance and virulence of foodborne pathogens (Cataldo et Exposure of L. monocytogenes to sublethal environmental stress conditions can enhance the survival upon subsequent exposure to lethal conditions and virulence gene expressions (Ferreira et al, 2003;Kazmierczak et al, 2003). Recently, Olesen et al (2009) also showed that exposure of L. monocytogenes to 4.5% NaCl resulted in increased transcription of genes relevant for the invasion.…”
Section: Introductionmentioning
confidence: 99%